Effect of Nitrogen and Intercropping with Lablab Bean (Lablab purpureus) on Growth of Fodder Maize (Zea mays L.) Under Two Irrigation Frequencies * (University of Khartoum Journal of Agricultural Sciences, 2023)
A field experiment was conducted during 2000/01 and 2001/02winter seasons at the farm of the Faculty of Agriculture, University ofKhartoum, to study the effects of nitrogen and intercropping with lablabbean (Lablab purpureus) on growth of fodder maize under two irrigationfrequencies using a randomized complete block design. Irrigationintervals of 10 and 20 days were applied four weeks after planting.Nitrogen at a rate of 0 and 88 kg N/ha was applied two weeks aftersowing. Planting methods were pure stand of maize, alternating rows andalternating holes of maize and lablab bean. Nitrogen applicationsignificantly increased, LAI in the second season. It reduced days to 50%tasseling and silking significantly. Intercropping significantly increasedplant height and shoot dry weight in the second season, but reduced LAIsignificantly during both seasons. Days to 50% tasseling and silking werenot affected by intercropping. Prolonging irrigation interval to twentydays had no significant effect on most vegetative growth parameters;however, it reduced days to 50% silking significantly. Plant populationwas, also, not affected by irrigation intervals.
Keywords: Maize; lablab; irrigation frequency; nitrogen fertilization; intercropping